Modelagem da estimativa da área foliar de leguminosas forrageiras e utilização do calopogônio em pastagens consorciadas - Homem, Bruno Grossi Costa (2016)
The aim of this study was to define defoliation strategies to balance the development of Calopogonium mucunoides cv. Common (Calopo), when mixed with Brachiaria brizantha cv. Marandu (Marandu palisadegrass); and develop and validate mathematical models to estimate efficiently the leaf area of legumes. The experiments were conducted at Federal University of Lavras, MG- Brazil. In the modeling experiment, the procedure was divided into two stages. In the first one, 586, 578, 604 and 583 leaves of Calopogonium mucunoides, Neonotoniawightii, Arachis pintoi and Stylosantes spp. were used to estimate leaflet and leaf area by modeling. In the second stage, to evaluate the symmetry of the initial leaflets of C. mucunoides, N. wightii, A. pintoi, Stylosantes spp. and A. pintoi terminals, besides the validation of the generated models, 200 leafs of each species were harvested. In both stages, length (L), width (W) and leaf area of all leaflets were measured. In the mixed pasture experiment, the experimental design was in randomized blocks, and three defoliation frequencies were studied at variable intervals, represented by the time at which the canopy reaches 90% (90LI), 95% (95LI) and 100% (100LI) interception of incident light, and a treatment without conducting grazing in free growth (FG), with four replications. In both periods, herbage mass, canopy structure, forage accumulation and stocking rate were estimated. The exponential model of convergence was adequate to estimate the area of the leaflets. It identified the equality between the pairs of initial leaflets of C. mucunoides, N. wightii, A. pintoi, Stylosantes spp. and A. pintoi terminals. On the other hand, for the mixed pasture experiment, the pre-grazing larger masses of grasses and legumes were obtained in the treatments 100LI and FG (P=0.0033 and 0.0016, respectively). In the post-grazing, a greater mass of grass was obtained by the frequency defoliation 90LI (P=0.0424). However, the mass of legumes between treatments was similar (P=0.8200), and the measure of frequency defoliation was lower; there was an increase in defoliation intensity, causing greater stress on legumes for grazing or trampling. Therefore, to measure elongation or senescence of legume leaves, using the exponential convergence model enables increased accuracy in the estimate of the area of the leaflets and is recommended as a management target of mixed pasture of Marandu palisadegrass with Calopo frequencies of defoliation 90% light interception.